Underwriting Operations and Financial Performance: Evidence from Non-Life Insurance Firms in Nigeria - Taiwo Olarinre Oluwaleye; Sunday Stephen Ajemunigbohun; Kehinde Emmanuel Abiodun (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
This study investigated the relationship between underwriting operations and the performance of non-life insurance firms in Nigeria. Specifically, the study examined the combined metrics of claim ratio, insurance premium, and re-insurance claims on the return on assets using the non-life insurance firms as bases in Nigeria. The study engaged data within the period of 2011-2020 extracted from the financial statements of five selected non-life insurance firms and analysis of data was conducted with a panel regression procedure. The result showed that insurance premium had a positive significant effect on return on asset, while re-insurance claim and claim ratio had positive but insignificant effect on return on asset. Therefore, this study concluded that underwriting operations contribute to the performance of non-life insurance firms in Nigeria. Hence, this study recommended that non-life insurance firms should put more effort into harnessing strategies and resources that enhances insurance premium in order to improve financial performance.